Infrared spectroscopy of Plio-quaternary sediments, from Lima river basin and Alvarães basin (Portugal) - Alves, M. I. Caetano (1991)
[Excerpt] Introduction This paper purposes to study gibsite and kaolinite cristallinity, present in Plio-quaternary fluvial sediments and in a colluvium (12A.PL.2), from Lima river basin and Alvarães basin, Minho region, Portugal NW.